2021
DOI: 10.3389/fpsyg.2021.678397
|View full text |Cite
|
Sign up to set email alerts
|

From Therapeutic Factors to Mechanisms of Change in the Creative Arts Therapies: A Scoping Review

Abstract: Empirical studies in the creative arts therapies (CATs; i.e., art therapy, dance/movement therapy, drama therapy, music therapy, psychodrama, and poetry/bibliotherapy) have grown rapidly in the last 10 years, documenting their positive impact on a wide range of psychological and physiological outcomes (e.g., stress, trauma, depression, anxiety, and pain). However, it remains unclear how and why the CATs have positive effects, and which therapeutic factors account for these changes. Research that specifically f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 183 publications
(368 reference statements)
6
81
0
8
Order By: Relevance
“…The language and process of art making are important resources for therapeutic care ( 184 , 185 ). Reflecting on 3 years of experience with art therapy in palliative care, Bras et al ( 186 ) suggested that medical professionals and patients can adopt the language of art, not only as a means for providing patients therapeutic relief, but also as a means to raise public awareness, and facilitate communication among patients, medical professionals and others involved in decision making about pain.…”
Section: Implementing Play As a Tool For Ict-based Citizen Sciencementioning
confidence: 99%
“…The language and process of art making are important resources for therapeutic care ( 184 , 185 ). Reflecting on 3 years of experience with art therapy in palliative care, Bras et al ( 186 ) suggested that medical professionals and patients can adopt the language of art, not only as a means for providing patients therapeutic relief, but also as a means to raise public awareness, and facilitate communication among patients, medical professionals and others involved in decision making about pain.…”
Section: Implementing Play As a Tool For Ict-based Citizen Sciencementioning
confidence: 99%
“…Research has demonstrated that integrating artistic practices into rehabilitative treatments through which patients are able to create or co-create art themselves improves patient-physician communication, facilitates patient thinking, and improve clinical outcomes (Sonke, 2016). Additionally, creative arts therapies have been shown to positively impact various psychological and physiological outcomes through the interactive processes of action and experiential-based training (King and Pascuzzi, 2018;de Witte et al, 2021). Initial creative arts therapy practices have been redefined through various interdisciplinary and collaborative efforts to maintain a focus on enhancing and humanizing the healthcare environment (Sonke, 2016).…”
Section: Creative Approaches To Interface Affordancesmentioning
confidence: 99%
“…Initial creative arts therapy practices have been redefined through various interdisciplinary and collaborative efforts to maintain a focus on enhancing and humanizing the healthcare environment (Sonke, 2016). More recently, research on clinical and evidence based creative expression in the form of creative arts therapies, which includes art and music therapies, has demonstrated the potential for better understanding of specific health conditions while offering a safe and cost-effective intervention as an adjunct to traditional medical management de Witte et al, 2021;King and Parada, 2021).…”
Section: Creative Approaches To Interface Affordancesmentioning
confidence: 99%
“…The therapeutic processes are led by certified arts therapists and are grounded in the triangular relationship between the therapist, the client, and the art process and product [ 2 ]. As in other psychotherapies, establishing a safe environment and therapeutic alliance are central factors in the therapeutic relationship in CAT [ 3 ]. The aim of the current study was to explore the experiences of older adults who participated in an online therapeutic creative process of digital photocollage as a tele-CAT intervention during a period of social distancing.…”
Section: Introductionmentioning
confidence: 99%
“…There are several change factors in CAT which distinguish it from verbal psychotherapy [ 3 ]. During the creative process of art making, the physical senses are engaged through relationships with paint, clay, images, movements and sounds.…”
Section: Introductionmentioning
confidence: 99%